Acute Renal Injury in patient With Severe Acute Pancreatitis - Pooran Mal, Ghulam Fareed, Nand Lal Seerani, A. H. Pathan, A. S. Memon, S. N. Khatti, M. K. Shaikh, Samar Raza, S. Z. A. Shah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of acute renal injury in patients with severe acute pancreatitis Methods: It is an observational research where patients coming at tertiary care hospital analyzed as severe acute pancreatitis of either gender were examined. Acute pancreatitis was determined when patients introducing to have pain in abdomen, ascend in serum amylase or potentially lipase > multiple times of ordinary reach and radiological discoveries reminiscent of acute pancreatitis. Acute kidney injury (AKI) was named when individuals with past ordinary renal capacity created decay of renal capacities with ascend in creatinine >2 mg/dl with decrease in urine output to under 0.5mg/kg/hr for 6 hours or more. Results: In our study out of fifty patients of severe acute pancreatitis 20 (40%) were males and 30 (60%) females, 15 women had history of gallstones while the history of alcohol was observed in 10 males and 02 females. The mean age ± SD for whole population is 58.85 ± 8.52. The pain abdomen was present in all patients followed by vomiting in 80%, jaundice was present in 30% cases and fever in 28%. The acute kidney injury has been detected in 32 (64%) of patients and 16 (32%) patients required renal haemodialysis (replacement therapy). The mean ± SD of hemoglobin (g/dl), WBC (x103 cells per cumm), serum potassium, urea, creatinine and bicarbonate for AKI population is 9.52±3.21, 27.85±10.95, 5.63±2.73, 268±20.85, 12.94±8.53 and 15.73±92.21. The mean ± SD of days of kidney insult and haemodialysis sessions for AKI population is 12.75±96.62 and 6.86±4.85 while the frequency (and %) of circulatory failure and deranged INR have been observed in 12 and 21 AKI patients. Conclusion: AKI is an incessant complication of acute pancreatitis and normally creates after the malfunction of different organs.